Freedom of Expression In Indonesia’s Democratic System: A Fiqh Siyasah Analysis From The Perspective of Maqāṣid Asy-Syarī’ah - Ahmad Royhan (Siyasah Wa Qanuniyah, 2025)
This study examines freedom of expression in democratic systems from the perspective of maqāṣid asy-syarī‘ah, aiming to analyze the relevance and limitations of the right to express opinions for citizens and their relation to public welfare. The research employs a qualitative library research approach, reviewing classical and contemporary literature on Islamic law, political jurisprudence, the Indonesian constitution, and democratic principles. Analysis focuses on identifying relevant concepts, values, and normative arguments linked to the protection of religion, life, intellect, lineage, and property. The findings indicate that freedom of expression is a fundamental right enabling active citizen participation in public decision-making and governmental oversight. From an Islamic perspective, this right aligns with maqāṣid asy-syarī‘ah, particularly hifẓ al-‘aql, requiring responsible development of intellectual capacity. Freedom of expression is relative and must be exercised with ethics, law, and social responsibility, supporting the achievement of collective welfare without harming individuals or society.